Crushing behaviour of glass fibre/epoxy composite pipes: the effects of winding angles, ageing, and temperatures - Nurul Fitriah, Suhaimi (Universiti Malaysia Perlis (UniMAP), 2016)
Master of Science in Mechanical Engineering